2012
DOI: 10.1097/opx.0b013e318249d727
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations and Topography in Normal, Keratoconus-Suspect, and Keratoconic Eyes

Abstract: Although corneal vertical coma and, to a lesser extent, ocular vertical coma were found to be good indicators for the detection of keratoconic eyes, the traditional corneal topographic value such as the inferior-superior dioptric asymmetry remains an important predictor for identifying suspected keratoconus. However, ocular vertical coma and ocular higher order total root mean square also represent a good means of identifying suspected keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 34 publications
8
58
0
1
Order By: Relevance
“…Gordon-Shaag et al [39], reported that corneal higher order aberrations were found to be significantly higher for keratoconic than normal eyes, but for suspect keratoconus the results were mixed. Alio et al [24], has established corneal aberrometry as a potential diagnostic tool for diagnosing keratoconus especially coma-like aberrations.…”
Section: Discussionmentioning
confidence: 98%
“…Gordon-Shaag et al [39], reported that corneal higher order aberrations were found to be significantly higher for keratoconic than normal eyes, but for suspect keratoconus the results were mixed. Alio et al [24], has established corneal aberrometry as a potential diagnostic tool for diagnosing keratoconus especially coma-like aberrations.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesize that, given the atypically high rate of lower order aberrations, children from this population may have atypically high levels of HOAs if astigmatic corneas are associated with other surface irregularities, as is seen in keratoconus. 6 We were specifically interested in the relation between astigmatism and the two HOAs that typically contribute the most power in studies of populations: unsigned spherical aberration (z12u) and unsigned coma (root-mean-square z07u and z08u).…”
mentioning
confidence: 99%
“…The total root mean square (RMS) of the higher order aberrations 17 of nine eyes of seven subjects was compared with and without the RGP scleral contact lens correction Finally, we report the general comfort and satisfaction levels of the subjects using these novel lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The corneal distortions included advanced KC, postpenetrating keratoplasty or KC with other surgical complications. Inclusion criteria for manifest KC were presence of paracentral steepening of the cornea or irregular bowtie astigmatism on topography (video keratoscope), and at least one of the following signs: Stromal thinning, Fleischer's ring or Vogt's striae observed by slit-lamp examination (adapted from Gordon-Shaag et al); 17 and a cone apex equal to or larger than 50 DS, and inferior superior dioptric difference equal to or above 3.5 DS (adapted from Millodot et al). 18 The study protocol was approved by the Hadassah Academic College Ethics Committee and subjects signed a statement of informed consent prior to their participation in the study.…”
Section: Subjectsmentioning
confidence: 99%